HAKEKAT DAN SISTEM NILAI DALAM KONTEKS PENDIDIKAN - Muhammad Isnaini; Khojir Khojir (Cross-border, 2021)
The essence of education is an effort that is carried out in a planned manner as a process of human interaction with the environment in order to develop self-potential, norms, good morals, to achieve the desired goals. Likewise, in the context of education, the values in question contain the meaning of goodness and truth which become references and guidelines in family, community, cultural and religious life. Therefore, each individual as much as possible can mingle with other individuals. Human mingling in a particular community is inseparable from the rules and norms that apply and a value that accompanies it. With this value a person can be said to be good or considered otherwise. To understand the meaning of a value, it is the role of education that really determines it.